Gesture controlled hospital beds for home care - Fudickar, Sebastian; Isken, Melvin; Fleßner, Jannik; Volkening, Nils; Steen, Enno-Edzard; Hein, Andreas (Ambient Assisted Living 9. AAL-Kongress, Frankfurt/M, Germany, April 20 - 21, 2016, 2017)
This article introduces a gesture-based user interface for hospi-tal beds that enables caregivers to focus on their patients and interact with them with both hands during mobilizing or transferring them. Gestures are detected either via static (96% sensitivity) or dynamic gestures (67.5 % sensitivity) and might be corrected by an extra repetition. Once gestures are correctly detected, caregivers can trigger bed movements via a foot switch as a hands-free operation, which as well functions as a dead man button. The evaluation of the usability through interviews with caregivers highlighted the system's general applicability, but as well some future challenges that have to be solved in order to achieve a system for every-day use.
(in press)